Influence of the operating temperature on the performance of silicon based photoelectrochemical devices for water splitting. (February 2016) - Urbain, Félix; Becker, Jan-Philipp; Smirnov, Vladimir; Ziegler, Jürgen; Yang, Florent; Kaiser, Bernhard; Jaegermann, Wolfram; Hoch, Sascha; Maljusch, Artjom; Rau, Uwe; Finger, Friedhelm
Abstract: This paper highlights the effect of the operation temperature on the performance of a photovoltaic-biased electrosynthetic cell (PV-EC) device for solar hydrogen production based on a triple junction thin film silicon solar cell. The influence of the temperature in the range from 25 °C to 60 °C was studied individually for all components of the device: the solar cell, the hydrogen evolving cathode, the oxygen evolving anode, and the electrolyte. Based on the experimental data, the overall temperature-dependent current–voltage characteristics of the complete PV-EC device was modeled by merging the current–voltage characteristics of the individual components in an empirical series circuit model. We found that a decrease in the photovoltage of the solar cells with increasing temperature can be compensated by an improved electrochemical kinetics with temperature. This lead to a slight improvement in the performance of the integrated PV-EC device. Under an assumption of 100% faradaic efficiency, a maximum solar-to-hydrogen efficiency of 9.5% was found in 1 M KOH at an operation temperature of 50 °C.